Protease-Activated Receptor 1 and 4 Signal Inhibition Reduces Preterm Neonatal Hemorrhagic Brain Injury. Issue 6 (June 2015) - Lekic, Tim; Klebe, Damon; McBride, Devin W.; Manaenko, Anatol; Rolland, William B.; Flores, Jerry J.; Altay, Orhan; Tang, Jiping; Zhang, John H.
Abstract : Background and Purpose—: This study examines the role of thrombin's protease-activated receptor (PAR)-1, PAR-4 in mediating cyclooxygenase-2 and mammalian target of rapamycin after germinal matrix hemorrhage. Methods—: Germinal matrix hemorrhage was induced by intraparenchymal infusion of bacterial collagenase into the right ganglionic eminence of P7 rat pups. Animals were treated with PAR-1, PAR-4, cyclooxygenase-2, or mammalian target of rapamycin inhibitors by 1 hour, and ⩽5 days. Results—: We found increased thrombin activity 6 to 24 hours after germinal matrix hemorrhage, and PAR-1, PAR-4, inhibition normalized cyclooxygenase-2, and mammalian target of rapamycin by 72 hours. Early treatment with NS398 or rapamycin substantially improved long-term outcomes in juvenile animals. Conclusions—: Suppressing early PAR signal transduction, and postnatal NS398 or rapamycin treatment, may help reduce germinal matrix hemorrhage severity in susceptible preterm infants. Abstract : Supplemental Digital Content is available in the text.